2020
DOI: 10.48550/arxiv.2007.15410
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scalability Analysis of Direct and Iterative Solvers Used to Model Charging of Non-insulated Superconducting Pancake Solenoids

M. Mohebujjaman,
S. Shiraiwa,
B. LaBombard
et al.

Abstract: A mathematical model for the charging simulation of non-insulated superconducting pancake solenoids is presented. Numerical solutions are obtained by the simulation model implemented on the Petra-M FEM platform using a variety of solvers. A scalability analysis is performed for both direct and preconditioned iterative solvers for four different pancakes solenoids with varying number of turns and mesh elements. It is found that even with two extremely different time scales in the system an iterative solver comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…For simulations of MHD systems, it is considered important to enforce the solenoidal constraint ∇ • B = 0 in discrete level to the machine precision [29]. This is because the condition is induced by the induction equation for all time if the initial magnetic field is divergence free [49], which is a precise physical law. Moreover, it has been shown that for MHD flow simulations ∇ • B = 0 can produce large errors in the solution [12].…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…For simulations of MHD systems, it is considered important to enforce the solenoidal constraint ∇ • B = 0 in discrete level to the machine precision [29]. This is because the condition is induced by the induction equation for all time if the initial magnetic field is divergence free [49], which is a precise physical law. Moreover, it has been shown that for MHD flow simulations ∇ • B = 0 can produce large errors in the solution [12].…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…The reduction of the nonlinearity implies the reduction of the test mass resonance frequency, which in turn increases the gravity gradiometer sensitivity at low frequencies. Finite element modeling is a powerful tool for modeling superconducting devices [23][24][25]. We set up a model with the finite element method in COMSOL Multiphysics ® simulation software and compared it with experimental results [26].…”
Section: Introductionmentioning
confidence: 99%
“…We will explore for more appropriate physical boundary conditions rather than the Dirichlet boundary conditions in Elsässer variables. It has been shown in [37], for Maxwell equations simulation, in presence of extremely different time scales, the iterative solver combination (FGMRES-GMRES) in conjunction with the parallel Auxiliary Space Maxwell (AMS) solver preconditioner outperforms over the direct solver. We plan to employ FGMRES-GMRES-AMS solver for solving complex problems using this scheme.…”
mentioning
confidence: 99%